ATP transients accompany spontaneous contractions in isolated guinea‐pig detrusor smooth muscle. Issue 11 (14th October 2019) - McCarthy, Carly J.; Marangos, Christos; Fry, Christopher H.; Ikeda, Youko
Abstract : New Findings: What is the central question of this study? Overactive bladder is associated with enhanced spontaneous contractions, but their origins are unclear. The aim of this study was to characterize the accompanying ATP transients. What is the main finding and its importance? Spontaneous detrusor contractions were accompanied by transient increases of ATP, and their appearance was delayed by previous activation of efferent nerves to the detrusor. This indicates that spontaneous ATP release from nerve terminals supports spontaneous contractions. ATP is a functional excitatory neurotransmitter in human bladder only in pathologies such as overactive bladder. A potential drug target is revealed to manage this condition. Abstract: Spontaneous contractions are characteristic of the bladder wall, but their origins remain unclear. Activity is reduced if the mucosa is removed but does not disappear, suggesting that a fraction arises from the detrusor. We tested the hypothesis that spontaneous detrusor contractions arise from spontaneous ATP release. Guinea‐pig detrusor strips, without mucosa, were superfused with Tyrode solution at 36°C. Preparations were subjected to electrical field stimulation (EFS; 3 s trains at 90 s intervals) to produce nerve‐mediated contractions, abolished by 1 µm TTX. Amperometric ATP electrodes on the preparation surface recorded any ATP released. Spontaneous contractions and ATP transients were recorded between EFS trains. Nerve‐mediated contractions were attenuated by atropine and α, β‐methylene ATP; in combination, they nearly abolished contractions, as did nifedipine. Contractions were accompanied by ATP transients that were unaffected by atropine but inhibited by TTX and greatly attenuated by nifedipine. Spontaneous contractions were accompanied by ATP transients, with a close correlation between the magnitudes of both transients. ATP and contractile transients persisted with TTX, atropine and nifedipine. Immediately after a nerve‐mediated contraction and ATP transient, there was a longer interval than normal before spontaneous activity resumed. Spontaneous contractions and ATP transients are proposed to arise from ATP leakage from nerve terminals innervating the detrusor. Extracellular ATP has a greater functional significance in humans who suffer from detrusor overactivity (spontaneous bladder contractions associated with incontinence) owing to its reduced hydrolysis at the nerve–muscle interface. This study shows the origin of spontaneous activity that might be exploited to develop a therapeutic management of this condition. Abstract :